2009
DOI: 10.1021/jp906144d
|View full text |Cite
|
Sign up to set email alerts
|

OH Radical Gas Phase Reactions with Aliphatic Ethers: A Variational Transition State Theory Study

Abstract: A theoretical study of the mechanism and kinetics of the OH radical reactions with aliphatic ethers is presented. Several methods were evaluated using the 6-311++G(d,p) basis set, with dimethyl ether as a test molecule. On the basis of the dimethyl ether results, the M05-2X functional was selected for the rest of the calculations. All the possible H abstraction paths have been modeled, and the importance of differentiating among H atoms bonded to the same C atom, according to their orientation with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 60 publications
6
91
1
Order By: Relevance
“…Tables 3 and 4 show the energies of the transition states evaluated at the QCISD(T)/6‐31G* level of theory for the attack of OH and Cl, respectively, at the various CH sites in 1,8‐cineole. Recent theoretical work has shown that the M05‐2X functional reproduces the experimental data available for the reactions of ethers+OH63 better than other methods of calculation.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 3 and 4 show the energies of the transition states evaluated at the QCISD(T)/6‐31G* level of theory for the attack of OH and Cl, respectively, at the various CH sites in 1,8‐cineole. Recent theoretical work has shown that the M05‐2X functional reproduces the experimental data available for the reactions of ethers+OH63 better than other methods of calculation.…”
Section: Resultsmentioning
confidence: 99%
“…M05-2X functional has been chosen as it yields satisfactory overall performance for the thermodynamic and kinetic calculations in organic and biological systems involving free radical reactions [3537]. Unrestricted wave function was employed for the open-shell system.…”
Section: Methodsmentioning
confidence: 99%
“…M05-2X has been proven to calculate kinetic data accurately. 50,51 Reliable wavefunction methods such as CCSD(T) can be used to obtain excellent energies, but incur problems from large spin contamination in the transition states at the UCCSD(T) level of theory. In our system, the S 2 values, spin contamination before and aer annihilation, range from 0.92 to 0.77 for IM1 at UCCSD(T)// M05-2X; this rate error is known to result from spin contamination, or the acceptable instrumental error of two experiments.…”
Section: Calculations Of Rate Constantsmentioning
confidence: 99%